2003
DOI: 10.1152/ajpendo.00535.2002
|View full text |Cite
|
Sign up to set email alerts
|

Protein acylation in the inhibition of insulin secretion by norepinephrine, somatostatin, galanin, and PGE2

Abstract: The major physiological inhibitors of insulin secretion, norepinephrine, somatostatin, galanin, and prostaglandin E 2, act via specific receptors that activate pertussis toxin (PTX)-sensitive G proteins. Four inhibitory mechanisms are known: 1) activation of ATP-sensitive K channels and repolarization of the ␤-cell; 2) inhibition of L-type Ca 2ϩ channels; 3) decreased activity of adenylyl cyclase; and 4) inhibition of exocytosis at a "distal" site in stimulus-secretion coupling. We have examined the underlying… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
25
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 46 publications
0
25
1
Order By: Relevance
“…After administration of insulin, the galanin mRNA levels in adrenals were maximally increased at 4 h, remained at maximal elevation for at least 48 h, and returned to baseline levels in 6 days (Anouar & Eiden 1995). Whereas an infusion of galanin, as mentioned above, caused a rapid, reversible, and dose-dependent reduction in basal insulin secretion from pancreatic islets via pertussis-toxinsensitive G proteins (Cheng et al 2003, Manabe et al 2003. Interestingly, the injection of galanin has an inhibitory effect on glucose-stimulated, but not L-arginineor potassium-stimulated, insulin release in animals (Yoshimura et al 1989) but fails to modify insulin secretion in man (Ghigo et al 1992).…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…After administration of insulin, the galanin mRNA levels in adrenals were maximally increased at 4 h, remained at maximal elevation for at least 48 h, and returned to baseline levels in 6 days (Anouar & Eiden 1995). Whereas an infusion of galanin, as mentioned above, caused a rapid, reversible, and dose-dependent reduction in basal insulin secretion from pancreatic islets via pertussis-toxinsensitive G proteins (Cheng et al 2003, Manabe et al 2003. Interestingly, the injection of galanin has an inhibitory effect on glucose-stimulated, but not L-arginineor potassium-stimulated, insulin release in animals (Yoshimura et al 1989) but fails to modify insulin secretion in man (Ghigo et al 1992).…”
Section: Discussionmentioning
confidence: 83%
“…of petussis-toxin-sensitive inhibitory GTP-binding regulatory protein (Cheng et al 2003, Manabe et al 2003. In the galanin-knockout mice, the initial short inhibition of insulin secretion was impaired, followed by an augmentation of insulin secretion when sympathetic and parasympathetic branches were chemically activated (Ahrén et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…It should also be noted that the direct application of long chain acyl CoA amplified the secretory response to Ca 2+ when capacitance was used as a measure of exocytosis and that the amplification was blocked by cerulenin [16]. Interestingly, there is evidence that protein acylation may be involved in the inhibition of insulin secretion by the physiological inhibitors norepinephrine, somatostatin, galanin and PGE 2 [20]. This suggests that in the same way, for example, that signaling through protein phosphorylation can have stimulatory or inhibitory effects within the cell depending upon their targets, so protein acylation may do likewise.…”
Section: Discussionmentioning
confidence: 99%
“…As protein acylation is a reversible process with dynamic cycles of acylation and deacylation [8,14] it is capable of playing a major role in signal transduction. It has been suggested that protein acylation plays a signaling role in the control of glucose-stimulated insulin secretion [15][16][17][18][19] and in the action of inhibitors of secretion such as norepinephrine [20]. In view of the importance of Ca 2+ -channels in the stimulation of insulin secretion [21][22][23][24][25][26] and the observation that Ca 2+ channels in bovine chromaffin cells are acylated [9], we studied the effects of two inhibitors of protein acylation, cerulenin and tunicamycin, on the activity of L-type Ca 2+ -channels in the β-cell line INS 832/13.…”
Section: Introductionmentioning
confidence: 99%
“…The amplifying incretin-like activity of LCFA has been proposed to reflect increased levels of endogenous LCFA-CoA in excess of those maintained by inhibition of ␤-oxidation by glucose-derived malonylCoA (3). LCFA-CoAs were assumed to directly modulate effector systems involved in GSIS (e.g., VGCC [11], protein kinase C [PKC] [12], exocytosis proteins [13]) or to serve as a precursor of respective signaling lipids (e.g., diacylglycerol, phosphatidylinositol 4,5-bisphosphate) (3). The incretin-like activity of LCFA-CoA has been proposed to be further complemented by activation of G-protein coupled receptor 40 (GPR40) by the free-acid form of LCFA (14 -16), resulting in Ca ϩ2 mobilization, PKC activation, cAMP-dependent protein kinase activation (4), and inhibition of voltage-gated outward K ϩ currents (17).…”
mentioning
confidence: 99%